Towards understanding the glacial impact on sedimentary basins using numerical methods - Zięba, Krzysztof Jan (NTNU, 2016)
The Cenozoic tectonism and the Pleistocene glaciations had a strong impact on the sedimentary basins and petroleum systems of the Barents Sea. The impact of these processes are often considered together resulting in an unclear understanding of the consequences of each process alone. This thesis focuses on the glacial impact on the sedimentary basins but it also provides an insight about the relative contribution of the glacial and pre-glacial processes to the net erosion, uplift, topography development and depletion of the hydrocarbon traps. Various numerical methods were used in this study. These include a novel approach used for determination of the glacial ages, a new Monte-Carlo-based method for estimating the erosion rates, flexural isostatic and hydrocarbon secondary migration modelling. The main results show that the western Barents Sea was glaciated during four marine isotope stages: MIS 16, MIS 12, MIS 6, and MIS 2, for a total duration of 29 kyr. During the first glacial event the study area was subjected to an erosion of 24.2 ± 8.5 mm/yr. After the first event the rates have significantly changed varying from -12.6 ± 1.6 mm/yr (net deposition) to 1.6 ± 1.8 mm/yr. The results show that in the proximal part of the Bear Island Trough Mouth Fan, the Pleistocene glacial contribution to the total net erosion was small. The most likely glacial contribution in this area reaches 100 ± 90 m, which is about 9% of the total net erosion. In the more distal part of the wedge, the glaciations did not contribute to the net erosion. The pre-glacial relief was modelled close to the sea level with the deepest parts at about 100 - 150 m below sea level and the shallowest at about 300 m above sea level. Between the Early and Middle Pleistocene the relief was deepened by 0 - 200 m. During the Middle-Late Pleistocene the shelf was deepened by up to 300 m in the troughs and up to 100 m on the banks. The Middle Pleistocene shelf represented shallow marine water depths with some elevated parts above the sea level. The model ...